An experimental investigation into enhancing oil recovery using smart water combined with anionic and cationic surfactants in carbonate reservoir - Shahla Kaabi Mofrad; Amir Hossein Saeedi Dehaghani (Energy Reports, 2020)
Among all EOR methods, chemical flooding using wettability alteration materials may be a promising choice to enhance oil recovery. The present study involves a combination of smart water and anionic and cationic surfactant injection as a new approach of EOR in an oil wet carbonate reservoir. CTAB as a cationic and SDS as an anionic surfactant were considered. The modified seawater from Persian Gulf was selected as the smart water. The effects of the smart water salt content and the concentration of the surfactants were measured. The optimum salt concentration of smart water was obtained when SW-3KCl, SW-1NaCl, and SW-4Na2So4 were used. Moreover, the optimum smart water combined with the surfactants was estimated to be 0.1CMC of SDS and 0.9 CMC of CTAB. The results showed that the combination of smart water and surfactants in carbonate reservoirs changed the wettability towards a water wet system. The oil recovery factor for distilled water, the seawater and the combination of smart water and the optimum surfactant concentrations were calculated to be 28%, 42% and 58%, respectively. The combination of smart water and surfactant had more oil recovery compared to an individual surfactant or smart water flooding.
Keywords: 330; Enhanced oil recovery; Interfacial tension (IFT); Smart water; Surfactant flooding